Itraconazole cis-diastereoisomers activate aryl hydrocarbon receptor AhR and pregnane X receptor PXR and induce CYP1A1 in human cell lines and human hepatocytes - Stepankova, Martina; Pastorkova, Barbora; Bachleda, Petr; Dvorak, Zdenek (Toxicology, 2017)
Triazole antimycotic itraconazole contains in its structure three chiral centres; therefore, it forms eight stereoisomers. Commercial preparations of itraconazole are a mixture of four cis-diastereoisomers. There is much evidence that efficacy, adverse effects, and toxicity of chiral drugs may be stereospecific. Therefore, we have prepared 4 pure cis-diastereoisomers of itraconazole and investigated their effects on transcriptional activities of xenoreceptors aryl hydrocarbon receptor AhR and pregnane X receptor PXR. Gene reporter assays showed that itraconazole dose-dependently activated both AhR and PXR, and the activation of AhR but not of PXR was enantiospecific. Itraconazole diastereoisomers transformed AhR and PXR into their DNA-binding forms, as demonstrated by electromobility shift assays. Cytochrome P450 CYP1A1 mRNA and protein were induced by itraconazole diastereoisomers in human hepatoma cells HepG2, human skin cells HaCaT, and in primary human hepatocytes. The expression of CYP3A4 in human intestinal LS180 cells was not influenced by itraconazole, but we observed downregulation of CYP3A4 in human hepatocytes. Collectively, we show that itraconazole is a dual activator of AhR and PXR, with differential effects on the target genes for xenoreceptors. The enantiospecific pattern was observed only in gene reporter assays for AhR. The data presented here might be of toxicological and clinical importance.
Keywords: inhibitory cytochromu P450 CYP3A; Cell Survival; Xenoreceptors; Antifungal drug; Pregnane X Receptor; stereoizomerie; Humans; Human hepatocytes; messenger RNA; Gene induction; receptory aromatických uhlovodíků; lidé středního věku; antifungální látky; Diastereoisomers; Cytochrome P450; Female; viabilita buněk; pregnanový X receptor; itrakonazol; lidé; Stereoisomerism; buněčné linie; Cytochrome P-450 Enzyme System; RNA, Messenger; Receptors, Steroid; ženské pohlaví; Cell Line; Antifungal Agents; Middle Aged; steroidní receptory; Receptors, Aryl Hydrocarbon; nádorové buněčné linie; Itraconazole; Hepatocytes; Cell Line, Tumor; Cytochrome P-450 CYP3A Inhibitors; hepatocyty; systém (enzymů) cytochromů P-450